Understanding differential reductions in undernutrition among districts in Rwanda through the perspectives of mid‐level and community actors on policy commitment and policy coherence - Iruhiriye, Elyse; Frongillo, Edward A.; Olney, Deanna K.; Niyongira, Emmanuel; Nanama, Simeon; Blake, Christine E.; Rwibasira, Eugene; Mbonyi, Paul (Wiley, 2024)
Understanding the drivers of improvements in child undernutrition at only the national level can mask subnational differences. This paper aimed to understand the contributions of factors in the enabling environment to observed differences in stunting reduction between districts in Rwanda. In 2017, we conducted 58 semi-structured interviews with mid-level actors (n = 38) and frontline workers (n = 20) implementing Rwanda's multi-sectoral nutrition policy in five districts in which stunting decreased (reduced districts) and five where it increased or stagnated (non-reduced districts) based on Rwanda's 2010 and 2014/15 Demographic and Health Surveys. Mid-level actors are government officials and service providers at the subnational level who represent the frontline of government policy. Interviews focused on political commitment to and policy coherence in nutrition, and contributors to nutrition changes. Responses were coded to capture themes on the changes and challenges of these topics and compared between reduced and non-reduced districts. Descriptive statistics described district characteristics. Political commitment to nutrition was high in both reduced and non-reduced districts. Respondents from reduced districts were more likely to define commitment to nutrition as an optimal implementation of policy, whereas those from non-reduced districts focused more on financial commitment. Regarding coherence, respondents from reduced compared to non-reduced districts were more likely to report the optimal implementation of multi-sectoral nutrition planning meetings, using data to assess plans and progress in nutrition outcomes and integration of nutrition into the agriculture sector. In contrast, respondents from non-reduced districts more often reported challenges in their relationships with national-level stakeholders and nutrition and/or monitoring and evaluation capacities. Enhancing the integration of nutrition in different sectors and improving mid-level actors' capacity to plan and advocate for nutrition programming may contribute to reductions in stunting.